COVID-19 Outbreak and Financial Performance of Chinese Listed Firms: Evidence From Corporate Culture and Corporate Social Responsibility - Sun, Yunpeng; Li, Ying (Frontiers in Public Health, 2021)
Motivated from the shortage of the existing research studies on impacts of dangerously contagious diseases on firms’ financial performance, upon the quarterly data of 126 Chinese listed firms across 16 industries, this study sheds light on the impacts of Coronavirus (Covid-19) outbreak on their financial performance. Overall, the Covid-19 outbreak negatively reduced Chinese listed firms’ financial performance proxied by the revenue growth rate, ROA, ROE, and asset turnover. This outbreak’s negative effects on Chinese firms’ profitability were much smaller than on their revenue growth rates. While this outbreak’s negative effects on Chinese listed firms’ financial performance is bigger for those seriously affected industries like travel and entertainment, we do that the financial performance of medicine industry improves due to the Covid-19 outbreak. In the meanwhile, those listed firms located in high-risk regions suffer a bigger financial loss during the outbreak, and especially there is a strong Hubei effect. The corporate culture and CSR moderated the inverse relationship between this outbreak and Chinese firms’ financial performance. Findings of this study contribute to enrich the existing literature on impacts of the Covid-19 outbreak on firms’ financial performance worldwide and suggest helpful practical and theoretical implications.